Tree-Inspired Structurally Graded Aerogel with Synergistic Water, Salt, and Thermal Transport for High-Salinity Solar-Powered Evaporation - Xiaomeng Zhao; Heng Zhang; Kit-Ying Chan; Xinyue Huang; Yunfei Yang; Xi Shen (Nano-Micro Letters, 2024)
Highlights Inspired by transport system in trees, a two-way water and salt transport mechanism is realized in a structurally graded aerogel, enabling simultaneous fast water uptake and salt rejection. The horizontally aligned pore channels near the surface achieve excellent heat localization by maximizing solar absorption and minimizing heat loss. The integrated water, salt, and thermal transports impart an impressive evaporation rate of 1.94 kg m−2 h−1 in a 20 wt% NaCl solution for 8 h without salt accumulation.